The bioavailability of sustained release nicotinic acid formulations. - Neuvonen, P J (1991)
1. The bioavailability of three nicotinic acid formulations was investigated in a randomized cross-over study. 2. Single doses of nicotinic acid (500 mg) were given to seven healthy volunteers. The concentrations of nicotinic acid and its main metabolite nicotinuric acid were measured in serum up to 8 h and in urine up to 24 h. 3. The relative bioavailability of unchanged nicotinic acid from two slow release formulations compared with a rapid-release form was only 1% and 25%, respectively. Relative values of AUC (0.8 h) for nicotinuric acid were 15% and 58%, and relative urinary recoveries were 18% and 59%, respectively. Facial flushing was less when slow release formulations were used. 4. The bioavailability of unchanged nicotinic acid is low and the ratio of nicotinuric acid to nicotinic acid in serum and urine is high when slow release formulations are used.